Mitigation of Organophosphate Pesticide Pollution in Agricultural Watersheds - Şahin, Çağrı; Karpuzcu, M. Ekrem (Elsevier, 2020)
Adsorption and biodegradation processes for four organophosphate pesticides (chiorpyrifos, diazinon, fenthion, dichlorvos) in wetlands and agricultural drains in Meric-Ergene Basin, Turkey have been investigated. K-oc (organic carbon normalized partition coefficient) values for all pesticides except diazinon were higher in more aromatic Pamuklu Drain sediments, indicating the possible influence of aromaticity on the extent of adsorption. The average half-lives of pesticides in Gala Lake sediments and Pamuklu agricultural drain sediments ranged from 2.25 to 69.31 days with chlorpyrifos exhibiting the slowest biotransformation rate and dichlorvos having the fastest biotransforrnation rate. The presence of humic substances and hydroperiod of wetlands have been identified as possible factors that affected the behavior of organophosphate pesticides in this study. The results from this study provide insight into the constructed wetland design offered for the mitigation of organophosphate pesticides in the basin. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Wetlands; Agricultural pollution; Organophosphate pesticides; Biodegradation; Adsorption